Mapping of consumer satisfaction and analysis of the level of importance of travel components and service quality in travel companies that use bus transportation - Bambang Hengky Rainanto; Suci Sri Utami Sutjipto; Pingky Dezar Zulkarnain; Ales Sandra Filpina Nubatonis; Fransisca Givanya Pamela; Abdul Talib Bon; Jonathan van Melle; Bambang Rudyanto (Jurnal Pariwisata Pesona)
The number of tourism journeys conducted via bus has shown a steady increase over time. This growth is supported by improved accessibility between regions due to road infrastructure development and heightened consumer demand for bus-based tourism. This study aims to analyze the influence of service quality and travel components on customer satisfaction in travel companies that use bus transportation. The number of respondents studied was 119 with the qualification that they had traveled using a travel company in the last 1 year. This study uses the Important Performance Analysis (IPA) method with descriptive analysis to evaluate the level of importance and performance of various service and travel components. Data testing was carried out using Microsoft Excel software. The results of the study found important information that: 1) Service quality (X1) has a significant influence on customer satisfaction, 2) Travel components (X2) also have a significant influence on customer satisfaction, and 3) Service quality and travel components simultaneously affect customer satisfaction. Based on these findings, it is recommended for travel companies to focus more on improving service quality and travel components in order to increase customer satisfaction.